Tribal loyalty and its impact on the relationship between the style of leadership values and performance of workers - Mohamed, Abdel Nasser Hassan Salem; Tabek, Al Sitti Ruqaya Binti Al Jaj; bin Abdul Muttalib, Mahzan (Journal of Economic, Administrative and Legal Sciences, 2018)
This study aims to know the effect of the leadership style by the values on the performance of the municipal members and the members of consultation councils in Libya, the tribal loyalty as an influenced factor. This study adopted the qualitative approach to investigate the sample of the study. The random sampling was used in this study. 300 participants were used as a sample of the study according to Skran‘s table (2006). The results of the study confirmed that there is a positive significant correlation between the leadership styles by the value on the performance of the employees as well as to role of the tribal loyalty is as an effective factor. However, the results support the problem that is addressed in this study. That is, there is an effective relationship of the tribal loyalty as an effective factor on the employees’ performance when the members of the municipal councils and the consultation councils do not apply and aware of the effect of the leadership style by the values. This loyalty has an impact on the performance of the municipal council and the councils of consultation in the municipals and has an impact on their relationships. They are still influenced by the tribal environment and values   that surrounding the organization, which have a clear impact through the results that the researcher has come up with the results reflex the fanaticism and non-hierarchical tribal blocs within the organization which increase the administrative corruption and the weakness of performance of Libyan organizations.
Keywords: Leadership by values; tribal loyalty; tribal community; employee performance